On the problems of determining the trajectory of an aerial vehicle based on inertial navigation system data (MCIT: Proceedings of International scientific and practical conference, 2023)
Navigation in military UAVs requires the use of onboard inertial systems. An approach is proposed for noise filtering, refinement of initial and intermediate values when applying calculation algorithms based on the estimates of loads and angular velocity taken from sensors.
Keywords: inertial navigation system; accelerometer; gyroscope; orientation angles; aerial vehicle; trajectory